O estatuto da cidade e a elaboração de planos diretores: uma avaliação sobre a construção de espaços participativos em processos de planejamento urbano. - Menezes, Karina Rossana de Oliveira (2008)
The approval of the Estatuto da Cidade , in July 2001, had started the beginning of Brazil s urban planning democratization process, through the popular participation that is obligatory in the elaboration of the Planos Diretores . However, the profound structural problems of Brazilian society showed that the difficulties to face up to the participation s institution as an instrument of social acting in the local urban planning are enormous. These difficulties are expressed as much in the participation quality as in the spaces made for the participative process in a Plano Diretor . This dissertation consists in an evaluation of the spaces made for the popular participation in the elaboration of the Planos Diretores , having as a studied object the experience of the city of Maceó. In this study have been evidenced the most important elements which contributed directly or indirectly in these spaces construction process, such as the local social and political structures and the kind of participation resulting from Maceió s Plano Diretor elaboration process.